2021
DOI: 10.3390/cells10092387
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Accessory Gland: A Complementary In Vivo Model to Bring New Insight to Prostate Cancer

Abstract: Prostate cancer is the most common cancer in aging men. Despite recent progress, there are still few effective treatments to cure its aggressive and metastatic stages. A better understanding of the molecular mechanisms driving disease initiation and progression appears essential to support the development of more efficient therapies and improve patient care. To do so, multiple research models, such as cell culture and mouse models, have been developed over the years and have improved our comprehension of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 176 publications
(191 reference statements)
0
6
0
Order By: Relevance
“…Half of men between 70-80 years of age show histological evidence of malignancy in the prostate (Carter et al, 1990). The Drosophila accessory glands serve reproductive functions analogous to the mammalian prostate, raising the possibility that these tissues in aged adult animals could be useful models for prostate cancer (Corrigan et al, 2014; Ito et al, 2014; Leiblich et al, 2019; Rambur et al, 2020; Rambur et al, 2021; Wilson et al, 2017). The fly reproductive system contains two accessory glands that release seminal fluid components into the Ejaculatory duct, where the seminal vesicles and testes also deposit sperm and additional seminal fluid components (Adams and Wolfner, 2007; Bloch Qazi and Wolfner, 2003; Cridland et al, 2022; Heifetz et al, 2005; Lung et al, 2001; Ravi Ram et al, 2005; Schnakenberg et al, 2012; Wilson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Half of men between 70-80 years of age show histological evidence of malignancy in the prostate (Carter et al, 1990). The Drosophila accessory glands serve reproductive functions analogous to the mammalian prostate, raising the possibility that these tissues in aged adult animals could be useful models for prostate cancer (Corrigan et al, 2014; Ito et al, 2014; Leiblich et al, 2019; Rambur et al, 2020; Rambur et al, 2021; Wilson et al, 2017). The fly reproductive system contains two accessory glands that release seminal fluid components into the Ejaculatory duct, where the seminal vesicles and testes also deposit sperm and additional seminal fluid components (Adams and Wolfner, 2007; Bloch Qazi and Wolfner, 2003; Cridland et al, 2022; Heifetz et al, 2005; Lung et al, 2001; Ravi Ram et al, 2005; Schnakenberg et al, 2012; Wilson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, drosophila represents a strong model for deciphering mechanisms related to epithelial cancers, such as lung or colon cancer [ 25 , 26 ]. The accessory gland itself represents a functional equivalent of a prostatic acinus [ 27 , 28 , 29 , 30 , 31 ], and in the last few years, it has been used as a model to decipher molecular signatures and molecular mechanisms related to prostate cancer [ 24 , 32 , 33 , 34 , 35 , 36 ]. Furthermore, there is a strong conservation of cholesterol’s role and metabolism in this insect [ 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Drosophila accessory gland contains two types of secretory cells: namely, main cells, the most abundant cell type, and secondary cells, present in the distal tip of this organ ( Supplementary Figure S1 ). Previous analyses have shown that tumorigenesis in both organs, namely the human prostate and the Drosophila accessory gland, can be driven by similar mechanisms ( Ito et al, 2014 ; Wilson et al, 2017 ; Rambur et al, 2020 ; Rambur et al, 2021 ). The accessory gland is emerging as a useful model to study different aspects related to cancer initiation and progression ( Ito et al, 2014 ; Wilson et al, 2017 ; Rambur et al, 2020 ; Rambur et al, 2021 ; Box et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous analyses have shown that tumorigenesis in both organs, namely the human prostate and the Drosophila accessory gland, can be driven by similar mechanisms ( Ito et al, 2014 ; Wilson et al, 2017 ; Rambur et al, 2020 ; Rambur et al, 2021 ). The accessory gland is emerging as a useful model to study different aspects related to cancer initiation and progression ( Ito et al, 2014 ; Wilson et al, 2017 ; Rambur et al, 2020 ; Rambur et al, 2021 ; Box et al, 2022 ). The adult accessory gland is a postmitotic organ.…”
Section: Introductionmentioning
confidence: 99%